Daily Profit Analysis: Daily Productivity Scheduling with Multiple Linear Regression - Putra, Fredi Ganda; Syazali, Muhamad (Desimal: Jurnal Matematika, 2020)
The purpose of this study was to see which day factors (Monday, Tuesday, Wednesday, Thursday, Friday, Saturday, Sunday) had the greatest impact on the net income of a store. The method used is a quantitative method using multiple linear analysis. The results show that Monday is the most influential on profits